IMPLEMENTASI PROGRAM PENGENDALIAN BANJIR SUB KOMPONEN C DI KOTA SEMARANG (PROGRAM PERBAIKAN SISTEM DRAINASE KALI SEMARANG) - Persada, Yudha Bhakti; Rengga, Aloysius; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2015)
The high level of development in Semarang city can be likened as a double-edge knife. In one side, it has positive impacts, but in the other side it said the opposite. It can be negative for its environment. One of the problems which appeared is floods disaster which often hit in Semarang. The impact of floods can ruin the people activities. One of efforts that Semarang city Government (Pemerintah Kota Semarang) can do is the flood control program through improved drainage Kali Semarang. This program implemented since 2010 and estimated completion in 2015. This research implemented in Dinas PSDA and ESDM Semarang city as a responsible person from the Semarang city Government party. Pengembangan Penyehatan Lingkungan Pemukiman (PPLP) of Central Java Province officer as a responsible person also from Central Java Province and kelurahan Bandarharjo which passed by Kali Semarang. This research is based on the failure of the flood control indicator in the evaluation of RPKD 2014 period about flood control. The aims of this research are to describe The Implementation of Flood Control Program Sub-Component C in Semarang City (Improvement Drainage System Kali Semarang) also describe the driving factor and inhibiting execution in the Implementation Program of Flood Control Sub-Component C in Semarang (Improvement Drainage System Kali Semarang). 2 The result showed that in the implementation there are many cases which can obstruct program implementation. This case is caused by human resources factors, the implementation team of yet understood of the standard and target of the implementation program, and few of community’s participation which caused by social and economic condition. The recommendations which appropriate are socialization about standard and target to entire of the implementation program, the staffing should be appropriate according to the competence, and the community empowerment of disaster area to increase community participation.